Contribution of Counseling Assistance Services in the Support of the Students’ Acquisition of Life Skills among Public Secondary Schools in Moshi Municipality (International Journal of Scientific Research and Management (IJSRM), 2024)
The researcher aimed to investigate the extensiveness of counselling assistance services in supporting students’ selected life skills among public secondary schools in Moshi municipality. This study is anchored in Rational Choice Theory. The study utilized a mixed methods approach with a convergent design, focusing on a target population of 1516 individuals, including 1232 students, 17 teacher counselors, 249 teachers, 17 heads of schools, and 1 District Secondary Education Officer. The sample size was 131 respondents, comprising 1 District Secondary Education 5 heads of schools, 5 teacher counselors, and 120 students. Data collection methods included questionnaires, interview guides, and documentary analysis, with two schools used for pilot testing. The research instruments were validated, and the questionnaires had a Cronbach’s Alpha reliability coefficient of 0.781. The quantitative data was analyzed using descriptive statistics using SPSS, while the qualitative data was analyzed thematically, with the findings presented using words and verbatim quotes. The researcher adhered to ethical principles, including confidentiality, anonymity, and protection from harm, and the APA 7th edition format was used for referencing. The study found that counselling assistance services contribute to students self-directed and control with a total mean score of 4.2. In conclusion, the study has provided compelling evidence that counselling assistance services significantly contribute to students’ self-directedness and control. The study recommended that students should take full advantage of individual and group counselling sessions offered by their schools. Teacher counselors should continue to offer and expand workshops on a range of topics, including career exploration, college preparation, and life skills, to equip students with the knowledge and tools they need for future success